A novel nonlinear solution for the polygon scaled boundary finite element method and its application to geotechnical structures. (February 2017) - Chen, Kai; Zou, Degao; Kong, Xianjing; Chan, Andrew; Hu, Zhiqiang
Abstract: The polygon scaled boundary finite element method is semi-analytical and known for its high precision. However, the material nonlinearity cannot be maintained because this method uses an analytical solution in the radial direction. In this paper, a novel nonlinear algorithm is developed by introducing internal Gaussian points over a subdomain. The response of nonlinearity for a concrete-faced rockfill dam is modeled. The results correspond well with the results from finite element modelling, which demonstrates the method can be used to describe the nonlinear characteristics of geomaterials. Furthermore, this method offers promising flexibility for analyzing complex geometries without decreasing the precision.